2012
DOI: 10.1007/s11356-012-1121-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of sulfonamides antibiotics in lake water and sediment

Abstract: Degradation of three sulfonamides (SAs), namely sulfamethoxazole (SMX), sulfamethazine (SMZ), and sulfadimethoxine (SDM) in surface water and sediments collected from Taihu Lake and Dianchi Lake, China was investigated in this study. The surface water (5-10 cm) was collected from the east region of Taihu Lake, China. Two sets of degradation experiments were conducted in 3-L glass bottles containing 2 L of fresh lake water and 100 μg/L of individual SAs aerated by bubbling air at a rate of approximately 1.2 L/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 36 publications
1
27
0
3
Order By: Relevance
“…Apparently, the matrix itself has an influence on the elimination which seems to exceed the impact of anaerobic or aerobic conditions. In sediment samples, no pronounced differences were found for sulfamethazine elimination under sterile and non-sterile anaerobic conditions (Zhang et al, 2013). The authors concluded that the elimination mainly occurred due to abiotic processes.…”
Section: Trimethoprim and Sulfonamidesmentioning
confidence: 86%
“…Apparently, the matrix itself has an influence on the elimination which seems to exceed the impact of anaerobic or aerobic conditions. In sediment samples, no pronounced differences were found for sulfamethazine elimination under sterile and non-sterile anaerobic conditions (Zhang et al, 2013). The authors concluded that the elimination mainly occurred due to abiotic processes.…”
Section: Trimethoprim and Sulfonamidesmentioning
confidence: 86%
“…Indeed, Al-Ahmad et al (1999) observed weak biodegradability of sulfamethoxazole (SMX) on day 28 of incubation. The weak degradation of sulfonamides, therefore, could contribute to the inhibition of microorganism activity due to high primary concentrations of antibiotics (Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are a class of commonly used PPCPs used as human and veterinary medicine. Due to their pseudo-persistent nature and potential to cause antibiotic resistant bacteria and genes (Baran et al, 2006;Zhang et al, 2013;Guo et al, 2013), it is imperative to study the fate and transport of antibiotics and their impacts in the natural environment (Ge et al, 2009(Ge et al, , 2010Guo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%